Cross-cultural adaptation and content and semantic validation of the Difficult Intravenous Access Score for pediatric use in Brazil - Márcia Helena de Souza Freire; Cristina Arreguy-Sena; Paula Christina de Souza Müller (Universidade de São Paulo, 2017)
ABSTRACT Objective: present the cross-cultural adaptation and content and semantic validation of the Difficult Intravenous Access Score for current use in Brazil. Method: cross-cultural adaptation and validation study, structured in six phases: initial translation, synthesis of translations, back-translation, assessment of documents by expert committee of specialized judges, pretest and presentation of the documents to the expert judges and to the author of the original instrument. Twenty health professionals were randomly recruited from a public hospital in the South of Brazil, working in pediatrics, in order to assess the agreement level with the variables in the instrument. In addition, a convenience sample of 30 pediatric patients was selected for the face validation of the same instrument. Cronbach's alpha coefficient, simple and percentage frequencies, the Shapiro-Wilk and Fisher's exact tests were used for the data analysis and reliability measures. Results: the cross-cultural adaptation phases were executed with totally clear translated variables, demonstrating satisfactory results in the content and semantic validation process. Conclusions: the Difficult Intravenous Access Score was adapted and its content and semantics were validated. External clinical validity, measuring equivalence and reproducibility analyses are needed.